Bringing embodied approaches to on-campus research methods teaching for large STEM cohorts: design, challenges, learning - Nicola Tomlinson; Sarah Kneen (Journal of Learning Development in Higher Education)
In the post-pandemic world, Learning Development researchers have posited a ‘new hybrid era of teaching’, in which lessons from lockdown in best practice for online and remote teaching play a key role in increasing the inclusivity of higher education (Kantcheva and Bickle, 2023). At the same time, as many students have returned to campus, research has begun to interrogate the role that campus spaces and in-person interaction play in teaching and learning in this new era (Hrach, 2021; Cox et al., 2022). Whether through explicit pedagogical design or implicitly, courses with practical elements, particularly in many scientific disciplines, tend to favour principles of embodied learning through ‘learning-by-doing’. Courses incorporate hands-on interaction with laboratory equipment and social constructivist approaches through student co-creation (Deshmukh, 2021), the centrality of which to students’ professional training was made even more apparent during the move to remote learning. However, these same principles have not underscored the pedagogical approach to research methods education on the undergraduate Engineering degree programmes at the University of Manchester, which has typically been taught more didactically in recent years. This lecture-format approach has been used partially due to challenges of practicality, with the course unit being delivered to a large cohort that can reach 500 students in a typical year. With these principles in mind, this academic year, the Library Teaching, Learning and Students team has collaborated with academic leads across Engineering disciplines to deliver embedded research methods workshops that incorporate elements of an embodied, social constructivist approach, playing to the unique strengths of in-person group learning. This presentation charted the process of Learning Developers and academic staff co-designing these workshops, highlighting challenges encountered, and outlining learning from the process to take forward into future collaborations with disciplines with large cohorts.